Cobalt–Nitrogen Co‐doped Carbon Nanotube Cathode Catalyst for Alkaline Membrane Fuel Cells. Issue 9 (5th August 2016) - Kruusenberg, Ivar; Ramani, Dilip; Ratso, Sander; Joost, Urmas; Saar, Rando; Rauwel, Protima; Kannan, Arunachala M.; Tammeveski, Kaido
Abstract: A highly active state‐of‐the‐art catalyst was synthesized by cobalt–nitrogen co‐doping of multi‐walled carbon nanotubes (Co/N/MWCNT) as non‐precious metal catalyst using cobalt chloride and dicyandiamide by high‐temperature treatment. A range of physicochemical characterization methods were used to observe the surface structure and composition of the synthesized electrocatalyst material. The kinetics of the oxygen reduction reaction (ORR) on this catalyst material was studied in 0.1 m KOH solution by using the rotating‐disk electrode method. The Co/N/MWCNT catalyst showed excellent electrocatalytic activity for ORR in alkaline media. In addition, the performance of the catalyst in a fuel cell was evaluated by fabricating membrane electrode assemblies employing a Tokuyama® anion exchange membrane (AEM), with hydrogen and oxygen gases at various temperatures. AEM fuel cell with Co/N/MWCNT cathode catalyst exhibited a power density of 115 mW cm −2 with H2 /O2 gases (100 % RH) at ambient pressure at 50 °C. Abstract : Not precious? Cobalt‐containing nitrogen‐doped carbon nanotubes are employed as non‐precious metal cathode catalysts for oxygen reduction reaction in alkaline membrane fuel cells. These catalysts exhibit high ORR activity in alkaline media and excellent fuel cell performance that is comparable to that of Pt/C catalysts.